ANALISIS YURIDIS TERHADAP GUGATAN DEBITUR ATAS DILAKSANAKANNYA LELANG EKSEKUSI HAK TANGGUNGAN DALAM PERKARA WANPRESTASI PADA KPKNL PEKANBARU - Ritonga, Almi Ramadhani; Purba, Hasim; Sidabariba, Burhan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The plaintiffs' lawsuit against the implementation of the mortgage execution auction occurred because the auction was sold at an unreasonable price. The sale of mortgage objects below market price is carried out if the object is not sold in the first sale, so the selling price must be lowered until the object is sold and the final sales value limit must not be below the liquidity value, as regulated in Article 49 of PMK Number 27 / PMK.06 / 2016 concerning Auction Implementation Guidelines. This study discusses three problems, namely: 1) Procedures for implementing mortgage execution auctions in default cases at the State Assets and Auction Service Office (KPKNL); 2) Legal protection for creditors and auction winners against debtor lawsuits regarding the implementation of mortgage execution auctions in default cases; and 3) Analysis of the judge's considerations on the decision of the Supreme Court of the Republic of Indonesia Number 1143 PK / PDT / 2022 concerning lawsuits for implementing mortgage execution auctions through public auctions.Keyword: Lawsuit, Execution of Mortgage Right Auction, State Property and Auction Service Office Abstrak: Gugatan para penggugat atas dilaksanakannya lelang eksekusi hak tanggungan, terjadi karena pelelangan tersebut dijual dengan harga yang tidak wajar. Penjualan objek hak tanggungan di bawah harga pasar dilakukan apabila dalam penjualan pertama objek tersebut tidak laku terjual, sehingga harga penjualannya harus diturunkan sampai objek tersebut terjual dan batas akhir nilai penjualan tidak boleh di bawah nilai likuiditas, sebagaimana diatur dalam Pasal 49 PMK Nomor 27/PMK.06/2016 tentang Petunjuk Pelaksanaan Lelang. Penelitian ini membahas tiga permasalahan, yaitu: 1) Prosedur pelaksanaan lelang eksekusi hak tanggungan dalam perkara wanprestasi pada Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL); 2) Perlindungan hukum bagi kreditur dan pemenang lelang terhadap gugatan debitur atas dilaksanakannya lelang eksekusi hak tanggungan dalam perkara wanprestasi; dan 3) Analisis pertimbangan hakim atas putusan Mahkamah Agung RI Nomor 1143 PK/PDT/2022 tentang gugatan pelaksanaan lelang eksekusi hak tanggungan melalui pelelangan umum.Kata kunci: Gugatan, Pelaksanaan Lelang Eksekusi Hak Tanggungan, Kantor Pelayanan Kekayaan Negara dan Lelang